Lymphoplasmacyte-Rich Meningioma of the Third Ventricle: Case Report - Ferreira, Marcelo Paglioli; Cambruzzi, Eduardo; Martins, Otávio Garcia; Gago, Guilherme; Vial, Antônio Delacy Martini (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Introduction Meningiomas are the most common primary intracranial tumors, accounting for up to 35% of the neoplasms in this category. Approximately 10–20% of these neoplasms are histologically atypical, and the lymphoplasmacyte-rich meningioma (LPM) corresponds to a very rare subtype of meningioma that is characterized histopathologically by massive infiltrates of inflammatory cells. The case described in the present study is the sixth case of an intraventricular LPM found in the literature and the first case considering the location in the third ventricle.Case Description A 21-year-old male without previous comorbidities sought medical attention due to visual impairment (complaining of intermittent visual blur) for 2 months. A magnetic resonance imaging of the brain confirmed the presence of a well-delimited solid mass in the third ventricle of 3.0 × 2.3 cm with a cystic component that extended itself inferiorly and distorted the visual pathway anatomy. Neurosurgeons decided to access the lesion using an interhemispheric transcallosal approach with a transforaminal access, and the lesion was resected completely. The patient has an ambulatorial endocrinological follow-up and is neurologically stable 6 months after the procedure. No new visual deficits were noted.Conclusion Lymphoplasmacyte-rich meningioma is a very rare intracranial tumor, and the involvement of the third ventricle make this case unique
Keywords: intracranial tumor; meningioma; lymphoplasmacyte-rich meningioma; intraventricular tumor; neuro-oncology